A novel non-invasive diagnostic approach based on urine and blood: a cross-sectional study combining lipoarabinomannan antigen and interferon-gamma release assay for active tuberculosis - Cai, Long; Zhu, Mingzhi; Fang, Tingting; Peng, Qianqian; Dai, Lingshan; Shao, YanQin; Liu, Libin (Frontiers in Immunology, 2026)
PurposeTo evaluate the diagnostic value of a combined strategy using the urine lipoarabinomannan (LAM) antigen assay and interferon-gamma release assay (IGRA) for active tuberculosis (TB), and to explore its potential as a non-invasive, sputum-independent diagnostic method for clinical application.Patients and MethodsA cross-sectional study design was adopted. Initially, 313 valid cases were selected for LAM performance evaluation, subsequently, 142 cases with both valid LAM and IGRA results were further selected from this group for combined test performance analysis. Using comprehensive clinical diagnosis as the reference standard, the diagnostic performance of LAM, IGRA, and two combination strategies (parallel: positive if either LAM or IGRA is positive; serial: positive only if both are positive) was evaluated, and their distribution characteristics in differentiating between tuberculosis and nontuberculous mycobacterial (NTM) infection were preliminarily explored.ResultsThe urine LAM assay demonstrated a sensitivity of 72% and a specificity of 79% for active TB. Its sensitivity was higher than that of smear microscopy (33%) and culture (56%), and slightly superior to Xpert MTB/RIF (69%) and TB-DNA (65%), although its specificity was lower. IGRA showed high sensitivity (92%) but moderate specificity (59%). The combination of LAM and IGRA significantly improved diagnostic performance: parallel testing achieved a sensitivity of 98%, making it suitable for TB screening and rule-out purposes, while serial testing increased specificity to 91%, supporting the confirmatory diagnosis of active TB. Among patients with NTM infection, the LAM+/IGRA− pattern accounted for 50% of cases, suggesting its potential utility in discriminating between TB and NTM infection.ConclusionThe combination of urine LAM antigen testing and blood-based IGRA optimizes TB diagnosis by simultaneously targeting two distinct dimensions: pathogen-derived antigens and host immune response. The parallel testing improves sensitivity for screening, while the serial testing enhances specificity for confirmatory diagnosis. This strategy offers a non-invasive approach with ease of sample collection, demonstrating particular value in diagnosing challenging cases such as sputum smear-negative pulmonary TB, extrapulmonary TB, and TB in immunocompromised patients.